MODEL ALTERNATIF PEMIDANAAN TERHADAP PENGGUNA NARKOTIKA DALAM RANGKA PEMBERANTASAN TINDAK PIDANA NARKOTIKA DI INDONESIA - Febby Widya; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Narcotics is on the one hand a useful drug or material in a field of medicine or health care and the development of science and on the other hand can also cause a very detrimental dependency if misused or used without strict and careful control and supervision. The importance of narcotics distribution needs to be closely monitored because currently there are many uses for negative things. The regulation regarding narcotics is regulated in Act Number 35 of 2009 concerning Narcotics. Even though the Law has included a threat which is burdensome for people who commit narcotic crimes, narcotics users do not feel deterrent or are afraid of the sanctions. In reality, sanctions imprisonment for narcotics users are not effective enough, it is proven that the number of narcotics users is increasing. Imprisoning narcotics users only makes things worse for them because of widespread corruption in prison. Prisoners can get whatever they want with money, including narcotics.This research uses the typology of normative legal research or also called doctrinal legal research, which is more specifically discusses the principles of law. In this study the authors use the nature of descriptive research, because the authors describe the Alternative Model of Criminalization against Narcotics Users in the Context of Eradicating Narcotics Crimes in Indonesia.The results of the research conducted by the author are, imprisonment given to narcotics abusers is considered ineffective to be given to narcotics abusers, therefore an alternative punishment is needed to be given to the narcotics abusers. This alternative is a form of criminal law policy that will later be made by the government. The alternative is in the form of social work crime and prioritizes rehabilitation of narcotics abusers. With the existence of a criminal law policy, it can be used as a foothold for law enforcement officials to be able to make rules that provide a deterrent effect to the perpetrators so that later perpetrators of the crime do not commit the same crime a second time.